Hierarchical MgAl‐layered double hydroxide growth on porous MgO template for pollution removal. Issue 6 (25th May 2022) - Li, Songnan; Mo, Tianyu; Chen, Lei; Zhang, Feng; Jamil, Saba; Lu, Yuli; Cai, Qinghai
Abstract: Different from alumina, magnesium oxide is seldom used in the synthesis of layered double hydroxide. In this work, MgAl layered double hydroxide with hierarchical structure was synthesized by using porous MgO as precursor via a facile in situ reaction at room temperature. And no chemical reagents are needed to provide an alkaline environment that allows precipitation to form during the synthesis process. Crystal structure, morphology, functional group, and surface features of the porous MgO precursor, the synthesized layered double hydroxide and its calcined product were characterized by X‐ray diffraction, Fourier transform infrared techniques. The results demonstrate that the synthesized layered double hydroxide is a pure phase and composed of nanosheets. Moreover, the synthesized layered double hydroxide inherits the morphology of the porous MgO precursor and forms a hierarchical structure. This structure has a large specific surface area (249 m 2  g −1 ) to increase the adsorption properties. Adsorption experimental results show that the maximum adsorption capacities of Congo red and Cr(VI) ions over the synthesized layered double hydroxide were 847.5 and 103.7 mg g −1, respectively. The adsorption process follows the Langmuir and pseudo‐second equation. Both adsorption processes were found to be spontaneous and endothermic.